Child labour in west Africa : the case of Côte d'Ivoire - (:unkn) unknown (My University, 2021)
The community-wide approach aims to eradicate child labor. This clearly displayed will comes up against several obstacles, both legal and structural in the African context. This thesis aims to show that the notion of child labor is not universally understood in the same way, particularly in West Africa and particularly in Côte d'Ivoire where this work is often synonymous with socialization. Also, we have shown that the issue is approached from the perspective of defending the rights of the child involved in work based on the International Convention on the Rights of the Child (ICRC). In addition, and in view of the current situation of children's rights, we proposed the ratification of international legal instruments by Côte d’Ivoire, in particular, the Optional Protocol on the sale of children, child prostitution and child pornography , the Optional Protocol to the Convention on the Rights of the Child on the involvement of children in armed conflict, the Convention on the Rights of Persons with Disabilities, International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families and Optional Protocol to the Convention on the Rights of the Child on a communications procedure would greatly contribute to this defense of children's rights.
Keywords: African Research